Euphol from Euphorbia tirucalli Negatively Modulates TGF-β Responsiveness via TGF-β Receptor Segregation inside Membrane Rafts. - Chun-Lin Chen; Ying-Pin Chen; Ming-Wei Lin; Yaw-Bin Huang; Fang-Rong Chang; Tsai-Hui Duh; Deng-Chyang Wu; Wei-Chiang Wu; Yu-Chen Kao; Pei-Hua Yang (PLoS ONE, 2015)
Transforming growth factor-β (TGF-β) responsiveness in cultured cells can be modulated by TGF-β partitioning between lipid raft/caveolae- and clathrin-mediated endocytosis pathways. Lipid rafts are plasma membrane microdomains with an important role in cell survival signaling, and cholesterol is necessary for the lipid rafts' structure and function. Euphol is a euphane-type triterpene alcohol that is structurally similar to cholesterol and has a wide range of pharmacological properties, including anti-inflammatory and anti-cancer effects. In the present study, euphol suppressed TGF-β signaling by inducing TGF-β receptor movement into lipid-raft microdomains and degrading TGF-β receptors.